2003
DOI: 10.1111/j.1365-2133.2003.05551.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous T-cell lymphoma and atopy: is there an association?

Abstract: No significant difference exists in the prevalence of atopy in Sézary or pre-Sézary syndrome compared with that in mycosis fungoides (chi2-test, P = 1.00). Furthermore, the rates of atopy in Sézary or pre-Sézary syndrome and mycosis fungoides are not significantly different from the prevalence of atopy in the general population (17-40%). On the basis of these observations, no evidence currently implicates a causal association of CTCL with atopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 36 publications
(75 reference statements)
1
26
0
Order By: Relevance
“…Therefore, the clinical and histologic differential diagnosis between CTCL and AD is sometimes very difficult. In addition, cases with CTCL proceeded by AD have been reported (6,7). We have reported that both CTCL and AD patients show elevated serum levels of CC chemokine ligand (CCL) 17, CCL27, CCL11, and CCL26, which may help explain some of the similar clinical, laboratory, and histologic features of these 2 diseases (8)(9)(10)(11)(12).…”
Section: Mycosis Fungoides (Mf) and Sezary Syndrome (Ss) Are The Mostmentioning
confidence: 81%
“…Therefore, the clinical and histologic differential diagnosis between CTCL and AD is sometimes very difficult. In addition, cases with CTCL proceeded by AD have been reported (6,7). We have reported that both CTCL and AD patients show elevated serum levels of CC chemokine ligand (CCL) 17, CCL27, CCL11, and CCL26, which may help explain some of the similar clinical, laboratory, and histologic features of these 2 diseases (8)(9)(10)(11)(12).…”
Section: Mycosis Fungoides (Mf) and Sezary Syndrome (Ss) Are The Mostmentioning
confidence: 81%
“…These agents, pimecrolimus and tacrolimus, are topical calcineurin inhibitor immunosuppressants (TCI) [1,2,3]. At the time of FDA marketing approval, concern was raised by the FDA that these agents might be associated with an increased risk of nonmelanoma skin cancer (NMSC) because oral versions of calcineurin inhibitors have been associated with an increased frequency of NMSC, especially in those who have received organ transplants [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Two cases of Sezary syndrome concerning a young man with severe AD have been published [8, 9]. However, in a retrospective study including 157 cases of CTCL, Mehrany et al[ 10] concluded that the association between atopic eczema and CTCL was not significant.…”
Section: Discussionmentioning
confidence: 99%